Hubungan Riwayat Reproduksi dengan Tumor Payudara pada Perempuan Usia Muda di Indonesia (Analisis Riset PTM 2016) - Rizqy Fauzia Ahsani; Putri Bungsu Machmud (Media Kesehatan Masyarakat Indonesia, 2019)
The incidence of breast tumor increases every year in Indonesia. At present, breast tumors do not onlyattack the elderly, but also at young age. Some studies show factors associated with breast tumors. Therefore,this study aimed to study the association of the reproductive history with tumor incidence in young women inIndonesia in 2016. This study used a cross-sectional study design and was conducted in December 2018-January2019 in the Faculty of Public Health of Universitas Indonesia using secondary data from the Riset PTM 2016(Non-communicable Disease Research 2016). The population in this study were all respondents of the 2016 PTMResearch. The sample was 14,891 respondents (total sampling) aged under 40 years who meet the inclusion andexclusion criteria. The variables used in this study were independent variables consisting of age of menarche, ageof first birth, marital status, breasfeeding history, the use of hormonal contraception; and the dependent variableis the incidence of breast tumors. The data was analyzed by chi square and logistic regression test. The resultsshowed an association between menarche age (OR=1,269), marital status (OR=1,353), breasteeding history(OR=1,295), and the use of hormonal contraception more than 5 years (OR=1,113) with breast tumors in youngwomen in Indonesia.